726 Leri-Weill Dyschondrosteosis - A Case of Complete Deletion of One of the Copies of Shox Gene. (October 2012) - Marques, J Sales; Pais, AI Pinto; Ferraz, L
Abstract : Introduction: Leri-Weill dyschondrosteosis (LWD), is a dominantly inherited skeletal dysplasia with disproportionate short stature owing to mesomelic shortening of the forearm and lower leg and Madelung deformity of the arm is found in 74% of children. SHOX mutations is found in 70% of cases. Case Report: Thirteen old month boy was admitted to genetic consultation because of short stature. The mother has disproportionate short stature. On physical examination, we found a phenotype similar with the mother, with short arms and lower legs. Height below the 5 th percentile. The skeletal x-ray confirmed mesomelic shortening of the forearm and lower legs. The x.ray did not demonstrated Madelung deformity of the arm. Molecular study using MLPA, confirmed complete deletion of one of the copies of SHOX gene - more than 440 Kb. Later on, we confirmed that he has growth hormone deficiency. The mother has also LWD. Discussion: LWD should be included in the diagnoses of short stature, especially if the child is disproportionate and has family history. In our case, because the mother is affected, the deletion of the SCHOX gene is inherited in the pseudoautosomal region of X chromosome. The transmission is pseudodominant and so the daughters of the index case will inherited the X chromosome of the father and will be affected. The boys will inherited the Y chromosome of the father. Prenatal diagnosis and genetic counseling is available for this syndrome. Treatment options include administration of recombinant growth hormone to improve final adult height.